Effects of dazomet combined with Rhodopsesudomonas palustris PSB-06 on root-knot nematode, Meloidogyne incognita infecting ginger and soil microorganisms diversity - Wang, Dongwei; Wang, Jian; Su, Pin; Dai, Jianping; Tan, Xinqiu; Zhang, Deyong; Liu, Yong; Cheng, Feixue (Frontiers in Microbiology, 2022)
Root-knot nematode, Meloidogyne incognita is one of the most important nematodes affecting ginger crop. Rhodopseudomonas palustris PSB-06, as effective microbial fertilizer in increasing plant growth and suppressing soil-borne disease of many crops has been reported. The combination of R. palustris PSB-06 and dazomet treatments had been proved to inhibit root-knot nematode on ginger and increase ginger yield in our preliminary study. The field experiments were conducted to elucidate the reasons behind this finding, and followed by next-generation sequencing to determine the microbial population structures in ginger root rhizosphere. The results showed that combination of R. palustris PSB-06 and dazomet treatment had a synergetic effect by achieving of 80.00% reduction in root-knot nematode numbers less than soil without treatment, and also could increase 37.37% of ginger yield through increasing the contents of chlorophyll and total protein in ginger leaves. Microbiota composition and alpha diversity varied with treatments and growth stages, soil bacterial diversity rapidly increased after planting ginger. In addition, the combined treatment could increase diversity and community composition of probiotic bacteria, and decrease those of soil-borne pathogenic fungi comparing to the soil treated with dazomet alone. Meanwhile, it could also effectively increase soil organic matter, available phosphorus and available potassium. Analysis of correlation between soil microorganisms and physicochemical properties indicated that the soil pH value and available phosphorus content were important factors that could affect soil microorganisms structure at the harvest stage. The bacterial family was more closely correlated with the soil physicochemical properties than the fungal family. Therefore, the combination of R. palustris PSB-06 and dazomet was considered as an effective method to control root-knot nematode disease and improve ginger soil conditions.